2007
DOI: 10.1373/clinchem.2006.081620
|View full text |Cite
|
Sign up to set email alerts
|

Gamma Glutamyltransferase and Long-Term Survival: Is It Just the Liver?

Abstract: Background: Increased gamma glutamyltransferase (GGT) is associated with cardiovascular disease. To date, however, few studies with sufficient sample size and follow-up have investigated the association of GGT with all-cause mortality. Methods: The relation of GGT to the risk of death was examined in a cohort of 283 438 first attendants (inpatients or outpatients) of the Vienna General Hospital with request for GGT analysis as part of a routine screening panel and was monitored for up to 13 years. To evaluate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
121
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(137 citation statements)
references
References 25 publications
15
121
0
1
Order By: Relevance
“…The study by Kazemi-Shirazi et al (23) investigated the association of GGT with the risk of mortality in a cohort of 283,438 first attendants (inpatients or outpatients). The median follow-up was 7.6 years.…”
Section: Ggt Cvd and Mortalitymentioning
confidence: 99%
“…The study by Kazemi-Shirazi et al (23) investigated the association of GGT with the risk of mortality in a cohort of 283,438 first attendants (inpatients or outpatients). The median follow-up was 7.6 years.…”
Section: Ggt Cvd and Mortalitymentioning
confidence: 99%
“…During follow-up, 4,884 (5.3%) incident cancers were observed. On average, 3.8 GGT measurements were obtained for each participant (range [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. Baseline GGT levels ranged from 3.0 to 590.7 U/L, with a median of 17.9 U/L.…”
Section: Characteristics Of Study Populationmentioning
confidence: 99%
“…Kazemi-Shirazi and colleagues 19 demonstrated a significant association of GGT levels and cancer death in a large, retrospective hospital-based study. In type 2 diabetic patients, Monami and colleagues 26 recently found an association between elevated GGT and cancer-related mortality; this relationship was confirmed in a multivariate analysis after adjustment for potential confounding.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Excess serum GGT has been linked to both oxidative stress [146] and increased cancer risk [147] as well as many other diseases [148]. In a study on 283 438 people who were divided into five subgroups based on GGT level, a hazard ratio of 18.5 for risk of hepatic carcinoma was ascertained for the highest level compared to the lowest [149]. Another study based in Korea found an increased risk of multiple cancers in association with elevated GGT: most especially liver cancer, but also cancer of the esophagus, larynx, stomach, bile ducts, lungs and colon [150].…”
Section: Colon and Liver Cancermentioning
confidence: 99%